Two-year survival of ART restorations placed in elderly patients: A randomised controlled clinical trial. Issue 4 (April 2015) - da Mata, Cristiane; Allen, P. Finbarr; McKenna, Gerald; Cronin, Michael; O'Mahony, Denis; Woods, Noel
Abstract: Objectives: Older dentate adults are a high caries risk group who could potentially benefit from the use of the atraumatic restorative treatment (ART). This study aimed to compare the survival of ART and a conventional restorative technique (CT) using rotary instruments and a resin-modified glass-ionomer for restoring carious lesions as part of a preventive and restorative programme for older adults after 2 years. Methods: In this randomised controlled clinical trial, 99 independently living adults (65–90 years) with carious lesions were randomly allocated to receive either ART or conventional restorations. The survival of restorations was assessed by an independent and blinded examiner 6 months, 1 year and 2 years after restoration placement. Results: Ninety-six (67.6%) and 121 (76.6%) restorations were assessed in the ART and CT groups, respectively, after 2 years. The cumulative restoration survival percentages after 2 years were 85.4% in the ART and 90.9% in the CT group. No statistically significant between group differences were detected ( p = 0.2050, logistic regression analysis). Conclusions: In terms of restoration survival, ART was as effective as a conventional restorative approach to treat older adults after 2 years. This technique could be a useful tool to provide dental care for older adults particularly in the non-clinical setting. (Trial Registration number: ISRCTN 76299321). Clinical Significance: The results of this study show that ART presented survival rates similar to conventional restorations in older adults. ART appears to be a cost-effective way to provide dental care to elderly patients, particularly in out of surgery facilities, such as nursing homes.